Comparison of Detection Methods for Premature Rupture of Membranes: IGFBP-1 Immunoassay Test vs. Nitrazine Test - Vekky Tria Novanda; Dovy Djanas; Ferdinal Ferry (Andalas Obstetrics And Gynecology Journal, 2025)
Objective: This study aimed to compare the diagnostic accuracy of the Insulin-like Growth Factor Binding Protein-1 (IGFBP-1) immunoassay test with the conventional Nitrazine test in detecting Premature Rupture of Membranes (PROM). Method: A diagnostic cross-sectional study was conducted as part of a multicenter study in 19 centers. It involved 40 pregnant women (20 with PROM and 20 without PROM) between 28–36 weeks of gestation at Dr. M. Djamil Hospital, Padang. The IGFBP-1 immunoassay (Actim PROM) and Nitrazine tests were performed using posterior vaginal fornix swabs. PROM diagnosis was confirmed by speculum examination. Data analysis included ROC curves, Youden’s Index, and AUC using SPSS v27. Result: The IGFBP-1 immunoassay yielded 100% sensitivity and 100% positivity in PROM cases. The Nitrazine test showed 75% sensitivity with 4 false negatives. IGFBP-1 provided more accurate results, was unaffected by vaginal bleeding or infections, but was more costly and required immediate handling. Conclusion: IGFBP-1 immunoassay demonstrates superior sensitivity and specificity compared to the Nitrazine test for PROM diagnosis. It is particularly advantageous in cases with unclear symptoms or contamination, supporting its use as a more reliable diagnostic tool in obstetric care.